SLC22A3 polymorphisms do not modify pancreatic cancer risk, but may influence overall patient survival - Mohelnikova-Duchonova, Beatrice; Strouhal, Ondrej; Hughes, David J; Holcatova, Ivana; Oliverius, Martin; Kala, Zdenek; Campa, Daniele; Rizzato, Cosmeri; Canzian, Federico; Pezzilli, Raffaele; Talar-Wojnarowska, Renata; Malecka-Panas, Ewa; et al. (Scientific reports, 2017)
Expression of the solute carrier (SLC) transporter SLC22A3 gene is associated with overall survival of pancreatic cancer patients. This study tested whether genetic variability in SLC22A3 associates with pancreatic cancer risk and prognosis. Twenty four single nucleotide polymorphisms (SNPs) tagging the SLC22A3 gene sequence and regulatory elements were selected for analysis. Of these, 22 were successfully evaluated in the discovery phase while six significant or suggestive variants entered the validation phase, comprising a total study number of 1,518 cases and 3,908 controls. In the discovery phase, rs2504938, rs9364554, and rs2457571 SNPs were significantly associated with pancreatic cancer risk. Moreover, rs7758229 associated with the presence of distant metastases, while rs512077 and rs2504956 correlated with overall survival of patients. Although replicated, the association for rs9364554 did not pass multiple testing corrections in the validation phase. Contrary to the discovery stage, rs2504938 associated with survival in the validation cohort, which was more pronounced in stage IV patients. In conclusion, common variation in the SLC22A3 gene is unlikely to significantly contribute to pancreatic cancer risk. The rs2504938 SNP in SLC22A3 significantly associates with an unfavorable prognosis of pancreatic cancer patients. Further investigation of this SNP effect on the molecular and clinical phenotype is warranted.
Keywords: duktální karcinom slinivky břišní; Male; Genetic Predisposition to Disease; Risk Factors; Organic Cation Transport Proteins; proteiny přenášející organické kationty; prognóza; Kaplan-Meier Estimate; Carcinoma, Pancreatic Ductal; Adult; Kaplanův-Meierův odhad; Aged; dospělí; mužské pohlaví; senioři; jednonukleotidový polymorfismus; zesilovače transkripce; Pancreatic Neoplasms; Polymorphism, Single Nucleotide; lidé; Enhancer Elements, Genetic; ženské pohlaví; Humans; nádory slinivky břišní; rizikové faktory; Prognosis; Female; lidé středního věku; genetická predispozice k nemoci; Middle Aged